Hakikat Pendidikan Inklusi Anak Usia Dini (PAUD) - Ayu Kurnia Wati; Mela Sintya; Sirly Afrilita; Surya Octa Fitriyani; Rendi Purnama Wulan; Fidhia Andani (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This Systematic Literature Review (SLR) aims to examine the essence of inclusive early childhood education (PAUD) as a foundation for holistic child development encompassing physical, cognitive, social, emotional, and moral dimensions. Using the PRISMA 2020 protocol, this study systematically analyzed 25 peer-reviewed journal articles with DOI published between 2021-2026 from Scopus-indexed databases. The findings indicate that inclusive PAUD significantly contributes to children's holistic development through differentiated learning strategies, adaptive curriculum, and collaborative approaches involving teachers, parents, and specialists. The study reveals that inclusive PAUD positively impacts physical-motor development (88.7%), social-emotional development (82.8%), and cognitive development (64.0%). However, challenges remain, including limited teacher competency, inadequate facilities, and insufficient government support. This study recommends strengthening teacher professional development, improving inclusive infrastructure, and developing contextually relevant inclusive education policies. Inclusive education in Early Childhood Education (PAUD) is an educational approach that provides equal opportunities for all children, including those with special needs, to receive educational services without discrimination. This concept is based on respect for diversity and the recognition that each child has different characteristics, abilities, and needs. The goal of inclusive education is to realize equal rights in education, optimally develop children's potential, foster tolerance and empathy, and create a welcoming and inclusive learning environment. The implementation of inclusive education in PAUD is characterized by child-centered learning, a flexible curriculum, the active participation of all students, and collaboration between teachers, parents, and the community. The presence of inclusive education benefits children's social, emotional, and academic development, while also fostering a culture that values differences from an early age. Thus, the essence of inclusive education in PAUD focuses not only on educational access for all children but also on efforts to create a fair and equitable learning environment that supports the development of each individual according to their potential.